Penguatan Produktivitas Karyawan dan Efisiensi Biaya Produksi untuk Mendukung Keberlanjutan Usaha Coffee Shop Skala Mikro - Dyan Fauziah Suryadi; Salmah Sharon (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
Micro-scale coffee shop businesses face challenges in sustaining operations, primarily due to labor constraints and suboptimal production cost control. This community service initiative aims to enhance the understanding and skills of the owner and employees of Ruang Teduh Coffee shop in Makassar regarding boosting work productivity, improving service quality, and implementing production cost efficiencies. The activity was conducted in six stages: initial observation, assessment of partner needs, material preparation, interactive training, simulation of waste identification, and development of an action plan. Participants included one business owner and three employees. Evaluation was carried out through observation, reflection, and assessment of outputs, such as simple performance indicators, a list of waste sources, and plans for recording raw materials and operational costs. The results indicate that participants were able to distinguish productivity as effective work rather than merely speed; agree on simple service indicators; identify sources of waste-such as unmeasured raw material usage, order errors, unsold products, and inefficient electricity and air conditioning usage; and formulate improvement measures, including daily raw material logging, stock control, and weekly cost evaluation. This initiative contributes to strengthening the managerial capacity of the micro-enterprise by integrating human resource management and production cost control methods that are simple, practical, and tailored to the partner's specific conditions.